Colombia : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2003)
This report examines the Observance of Standards and Codes on Fiscal Transparency for Colombia. Colombia has made considerable progress in improving transparency in public finances. Major initiatives include: adoption of the Presidential Anti-Corruption Plan; improvement in the management of public banks; clarification of the expenditure responsibilities and resources among different levels of government; and introduction of modern accounting procedures. The legislative agenda now under way could lead to the adoption of important standards in the area of fiscal responsibility and transparency, as well as the integration and strengthening of territorial legislation.